2012
DOI: 10.2165/11636270-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perception and Communication in Sub-Saharan Africa

Abstract: In this narrative review, a brief summary of theoretical approaches to risk perception is followed by an analysis of some of the special factors influencing risk perception and risk communication in sub-Saharan Africa. Examples of recent and emergent local medicines and vaccine controversies in several countries are given along with evidence and analysis of how they were managed. These demonstrate, among other things, the extent to which ethnic, religious and cultural issues influence popular perception, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The study found that complacency, high levels of illiteracy, multi-ethnic diversity, limited access to main and social media (especially in rural areas), a lack of alternatives (such as economic activities, water, food, scarcity of land), emotional attachment to place, limited access to experts who were perceived to be neutral, and lack of trust between locals and government officials were some of the main barriers to risk communication in the Niger Delta. These findings are similar to the study by Dodoo and Hugman (2012) who asserted that there is limited capacity for credible and reliable scientific assessment and public communication strategies in sub-Saharan Africa. In part, this reflects the relatively low levels of scientific literacy in the region and the power gradients that exist between local communities and the corporate-government nexus.…”
Section: Challenges and Barriers To Risk Communication In The Niger Dsupporting
confidence: 89%
“…The study found that complacency, high levels of illiteracy, multi-ethnic diversity, limited access to main and social media (especially in rural areas), a lack of alternatives (such as economic activities, water, food, scarcity of land), emotional attachment to place, limited access to experts who were perceived to be neutral, and lack of trust between locals and government officials were some of the main barriers to risk communication in the Niger Delta. These findings are similar to the study by Dodoo and Hugman (2012) who asserted that there is limited capacity for credible and reliable scientific assessment and public communication strategies in sub-Saharan Africa. In part, this reflects the relatively low levels of scientific literacy in the region and the power gradients that exist between local communities and the corporate-government nexus.…”
Section: Challenges and Barriers To Risk Communication In The Niger Dsupporting
confidence: 89%
“…Qualitative data furthermore facilitate the necessary grasp of everyday practices to assist in interpreting survey and secondary data in context [80]. The influence of health literacy on how people (do not) act on risk knowledge [2,13], legitimacy on HCPs' heeding of regulatory advice [69] and mistrust in industry and declining trust in regulators on trust-building strategies [23,47,81,82] are all subtle features of texture, noted within the pharmacovigilance literature, whereby the relationship between knowledge and behaviour is mediated by norms, emotions and what is meaningful for stakeholders (see 'Texture: methods and 'measurements'' section and wider literature e.g. [47,58,78]).…”
Section: Depth: Methods and Measurementmentioning
confidence: 99%
“…Engagement of stakeholders is emphasised by researchers and policymakers as a fundamental tool for enhancing pharmacovigilance processes [1][2][3][4][5][6][7]. Engaging patients and other medicines users (MUs), and healthcare professionals (HCPs)-as the stakeholders closest to the prescribing and use of medicines-can support pharmacovigilance systems [8,9] across various settings, e.g.…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…However, application of these documents in everyday pharmacovigilance has been a challenge. An issue of Drug Safety not long ago, dedicated to the theme of risk communication, discussed barriers to implementation and proposals for improving communication practices from worldwide experience [9][10][11][12][13][14][15][16][17]. There is much more research on medical information, communications and risk perception available, but every time a major safety concern arises with a medicine, designing a communication strategy and materials for avoiding and mitigating risks is perceived as a complex new challenge by both industry and regulatory authorities, and either the available evidence from the communication sciences is not fully applied or specific research to guide them is lacking.…”
Section: Focus On Risk Communicationmentioning
confidence: 99%